2015
DOI: 10.1155/2015/827027
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Tranexamic Acid in Reducing Blood Loss following Hip Reconstruction in Children with Cerebral Palsy

Abstract: This is a retrospective study of 51 consecutive hip reconstructions in children with cerebral palsy performed between 2011 and 2013. Tranexamic acid (TXA) was used in 14 hip reconstructions only. Transfusion rate was higher, postoperative Hb was lower, and patients stayed longer in the TXA group. This did not reach a statistical significance (P = 0.75, 0.5, and 0.71, resp.). More than half of the patients who had TXA underwent bilateral hip reconstructions in comparison with 27% only in the non-TXA group. Bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(53 citation statements)
references
References 18 publications
0
53
0
Order By: Relevance
“…[29][30][31] Its value in the other group, however, is less clear. 32 Recently, Bryan et al reported a benefit for TXA in reducing the need for transfusion in patients undergoing periacetabular osteotomies. 16 Intraoperative cell salvage is another tool to decrease the need for allogenic RBC transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31] Its value in the other group, however, is less clear. 32 Recently, Bryan et al reported a benefit for TXA in reducing the need for transfusion in patients undergoing periacetabular osteotomies. 16 Intraoperative cell salvage is another tool to decrease the need for allogenic RBC transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…TXA has been shown to be effective at reducing intraoperative blood loss and allogenic RBC transfusion rates in spinal corrective surgery, and its use has become common practice at our institution 29–31 . Its value in the other group, however, is less clear 32 . Recently, Bryan et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the two groups had intraoperative estimated blood loss (EBL) of 6 cc/kg to 6.5 cc/kg, which is less than half the mean EBL of 15.4 cc/kg reported by McNerney et al 9 The intraoperative EBL of 159 cc in our No TXA group is roughly half the 300 cc EBL reported by Kjeldgaard Pedersen et al 22 Finally, the total rate of transfusion in our non-TXA patients of 19.8% during their intra- and postoperative courses contrasts with transfusion rates of 37% to 67% reported in two previous studies. 8,9…”
Section: Discussionmentioning
confidence: 99%
“…Despite being well studied in the adult population, there is a paucity of literature investigating intraoperative treatment with TXA in patients with CP undergoing orthopaedic procedures. Majid et al 8 found in a retrospective study of 51 patients with CP undergoing hip reconstructive surgery that TXA use was associated with higher transfusion rates, lower postoperative haemoglobin values and longer hospital length of stays. However, patients who received TXA were more disabled based on the GMFCS and had twice as many bilateral hip reconstructions performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation